A critical evaluation of the interaction between sport and law in South Africa - Louw, Andre Mouton; Carnelley, M.(Marita), 1962-; Schembri, Christopher; Whitcher, Benita (Stellenbosch : Stellenbosch University, 2012)
Published in September 2009 as the monograph South Africa Supplement 15 in the series Blanpain, R & Hendrickx, F (ed.) International Encyclopaedia of sports law.' -- P. 3.